Studies on Synthesis of Some Novel Heterocyclic Chalcone, Pyrazoline, Pyrimidine - 2 - One, Pyrimidine - 2 - Thione, para-Acetanilide Sulphonyl and Benzoyl Derivatives and their Antimicrobial Activity - Rakesh N. Mistry; K. R. Desai (E-Journal of Chemistry)
1, 2 - Dichloro benzene on chlorosulphonation by chlorosulphonic acid gives 1, 2 - [dichloro] - benzene sulphonyl chloride which on condensation with p –amino acetophenone gives 1-[acetyl] - 1’ , 2’ - [dichloro] - dibenz sulphonamide derivative. This derivative undergo condensation with 2,4- dichloro benzaldehyde gives 1- [3” - (sub. phenyl) - 2” - propene - 1” - one] - 1’ , 2’ - [dichloro] - dibenz sulphonamide derivative which on reaction with 99% hydrazine hydrate and glacial acetic acid gives 1-[acetyl]-3- [1’ , 2’ - (dichloro) - dibenz sulphonamide] -5 - [2” , 4” - dichloro phenyl] - 2 - pyrazoline derivative. This derivative reacts with various substituted aldehydes to give corresponding substituted chalcone derivatives [1(a-j)]. Now, these chalcone derivatives [1(a-j)] on condensation with urea gives corresponding substituted pyrimidine - 2 - one derivatives [2(a-j)] and on condensation with thio-urea gives corresponding substituted pyrimidine- 2 -thione derivatives [3(a-j)]. Further, these chalcone derivatives [1(a-j)] on reaction with 99% hydrazine hydrate gives 1 - [1’ - (H) - 5’ - (sub. phenyl) - 2’ - pyrazoline]- 3 - [1” , 2” - (dichloro) - dibenz sulphonamide] - 5 - [2’’’ , 4’’’ - dichloro phenyl]-2- pyrazoline derivatives [4(a-j)] as an intermediate compounds, which on condensation with p-acetanilide sulphonyl chloride gives corresponding substituted p - acetanilide sulphonyl derivatives [5(a-j)] and on condensation with benzoyl chloride gives corresponding substituted benzoyl derivatives [6(a-j)]. Structure elucidation of synthesised compounds has been made on the basis of elemental analysis, I.R. spectral studies and 1H N.M.R. spectral studies. The antimicrobial activity of the synthesised compounds has been studied against the cultures “Staphylococcus aureus”, “Escherichia coli” and “Candela albicans”.